1996
DOI: 10.1128/mcb.16.4.1668
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Regulated Association of E2F1 and Sp1 Is Related to Their Functional Interaction

Abstract: Because of the large number of growth-regulated genes containing binding sites for the transcription factors Sp1 and E2F and the reported ability of E2F to mediate cell cycle (growth) regulation, we studied interactions between E2F1 and Sp1. In transient transfection assays using Drosophila melanogaster SL2 cells, transfection with both Sp1 and E2F1 expression vectors resulted in greater than 85-fold activation of transcription from a hamster dihydrofolate reductase reporter construct, whereas cotransfection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
204
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(210 citation statements)
references
References 51 publications
4
204
1
1
Order By: Relevance
“…Two reports describe a novel interaction between Sp1 and members of the E2F1 family, including the superactivation of Sp1-mediated transcription by E2F (Karlseder et al, 1996;Lin et al, 1996). Therefore, Sp1 is bound by both E2F and Rb proteins, each of which can increase Sp1-mediated transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reports describe a novel interaction between Sp1 and members of the E2F1 family, including the superactivation of Sp1-mediated transcription by E2F (Karlseder et al, 1996;Lin et al, 1996). Therefore, Sp1 is bound by both E2F and Rb proteins, each of which can increase Sp1-mediated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Sp1 interacts with other proteins such as p107 (Datta et al, 1995), p53 (Borellini and Glazer, 1993) and E2F (Karlseder et al, 1996;Lin et al, 1996); the interaction with p107 represses Sp1-dependent transcription whereas the interaction with E2F leads to synergistic activation of dhfr transcription. On the other hand, the tumor suppressor Rb is involved in the control of transcription of several genes.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation has been made with the murine promoter (Hsiao et al, 1994). Azizkhan's laboratory has shown that E2F-1 can transactivate the hamster dihydrofolate reductase (DHFR) promoter via its SP-1 site, when E2F-1 can directly interact with SP-1 factor (Lin et al, 1996). As the quail E2F-1 promoter possesses SP-1 sites, some of which are occupied in vivo, one might argue that the E2F-1 transactivation on the E2F site deleted promoter is due to the E2F-1/SP-1 complex bound on SP-1 sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned above, we can not exclude the possibility that Sp1 and Sp3 bound to the major Sp1 site cooperate with other -HSS 5 Figure 7 IdentiÂźcation of DNaseI hypersensitive sites in the 5'-anking region of the mouse HGF promoter. Freshly isolated nuclei from NIH3T3 Âźbroblasts were treated with the indicated amounts of DNaseI, then their genomic DNA was extracted, transcription factors bound to other sites in the 5'-anking region of the mouse HGF promoter, since it is known that Sp1 cooperates with several transcription factors such as p53 (Gualberto and Baldwin, 1996), GATA-1 (Merika and Orkin, 1995), YY1 (Seto et al, 1993), E1a (Wagner and Green, 1994) and E2F (Lin et al, 1996). Control of HGF gene expression is complex.…”
Section: Discussionmentioning
confidence: 99%